Physico-Chemical Quality Of Drinking Water From Various Sources In Abia State, Nigeria - Okereke, Eric E.; Obasi, Kalu O.; Amadi, Chinasa A.; Ede, Okorie A.; Aronu, Cecilia; Abonyi, Isaiah C.; Nwankwo, Chidiebere J.; Eze, Peter; Amadi, Agwu N. (Journal of Current Biomedical Research, 2022)
The majority of Nigerians lack access to a safe drinking water source, making sustainable and equitable access to safe drinking water a challenge. The current study was designed to evaluate the physicochemical quality of drinking water from various sources in 24 randomly selected communities throughout Abia State, Nigeria. These communities were selected from 8 Local Government Areas within the 3 senatorial zones of Abia State. Using sterile universal containers, water samples were collected from the major drinking water sources in the selected communities. On-site evaluation of the pH, electrical conductivity (EC), total dissolved solids (TDS) and temperature of the water samples was carried out using a HI9813-6 pH/EC/TDS/Temperature meter. The pH values of the water samples from all sampled communities ranged between 4.1 and 5.9, and the acidic pH levels of the water samples were not within the Nigerian Industrial Standard’s (NIS) approved range of 6.5 - 8.5. Furthermore, the water sources in the selected communities were found to have ambient temperatures ranging from 25.8 - 31.8oC. The average electrical conductivity (0.04 µS/cm) and total dissolved solids (36.4 mg/L) of water samples from all senatorial zones studied were both within acceptable limits of 1000 µS/cm and 500 mg/L respectively. Although the other parameters (temperature, EC and TDS) evaluated in this study were within acceptable limits for drinking water physicochemical quality, this study emphasizes the importance of effective water treatment, safe distribution to households, and continuous monitoring and quality assessment of drinking water sources in Nigeria.